Magneto-thermo-piezo-elastic wave in an initially stressed rotating monoclinic crystal in a two-temperature theory - Yadav, Anand Kumar (Zielona Góra: Uniwersytet Zielonogórski)
This research problem is an investigation of wave propagation in a rotating initially stressed monoclinic piezoelectric thermo-elastic medium under with the effect of a magnetic field. A two-temperature generalized theory of thermo-elasticity in the context of Lord-Shulman`s theory is applied to study the waves under the magnetic field.
Keywords: piezo-electricity; monoclinic; rotation; magnetic field; phase velocity; attenuation coefficient; specific loss; two-temperature